Thyroid disease in the perimenopause and postmenopause period - YOLDEMİR, AHMET TEVFİK; YAVUZ, DİLEK (TAYLOR & FRANCIS LTD, 2018)
The interpretation of thyroid function tests should be cautiously made during the perimenopause and postmenopause period bearing in mind that physiologic changes do exist in this group of women in terms of secretion and metabolism of thyrotropin and thyroid hormones. Moreover the incidence of thyroid disorders increases in postmenopausal and elderly women. There is no consensus for screening postmenopausal women even though there is well-known evidence about the effect of thyroid status on cognitive function, cardiovascular risk, bone turnover, and longevity. The diagnosis of any thyroid disorder is challenging in these patients because the symptoms are more subtle and attributed to menopausal symptoms. Management requires more attention in this population than that of younger groups, because high doses of L-thyroxine can lead to cardiac complications and increased bone turnover. Furthermore radio-iodine is preferred in treatment of hyperthyroidism in older patients. The risk of nodular thyroid disease and thyroid cancers increases in this group. Although the diagnostic approach is the same as for young patients, the risk of surgery is high and disease prognosis is worse. Women with any form of thyroid disease should be treated according to the current guidelines. Decision for menopausal hormonal therapy should be individualized regardless of the concomitant presence of thyroid disorders.
Keywords: Hypothyroidism; hyperthyroidism; thyroid cancer; menopause; CORONARY-HEART-DISEASE; SERUM THYROTROPIN; SUBCLINICAL HYPERTHYROIDISM; CARDIOVASCULAR EVENTS; COGNITIVE FUNCTION; FOLLOW-UP; ASSOCIATION GUIDELINES; STIMULATING HORMONE; PREDICTIVE-VALUE; NATURAL-HISTORY